2016
DOI: 10.1016/j.powtec.2015.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional full loop simulation of solids circulation in an interconnected fluidized bed

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 47 publications
(75 reference statements)
0
6
0
4
Order By: Relevance
“…With the development of the model and computing capacity, more and more investigators conducted full-loop simulation of the CFB system [14][15][16][17][18][19][20][21][22], which treats the CFB as a whole dynamic system. Chu et al [14] conducted a 3D full-loop simulation for CFB by means of the combined continuum and discrete method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of the model and computing capacity, more and more investigators conducted full-loop simulation of the CFB system [14][15][16][17][18][19][20][21][22], which treats the CFB as a whole dynamic system. Chu et al [14] conducted a 3D full-loop simulation for CFB by means of the combined continuum and discrete method.…”
Section: Introductionmentioning
confidence: 99%
“…The flow regime, especially choking and continuous transitions, was captured by simulation. Guan et al [16] conducted a full-loop simulation of a CFB including the riser, bubbling bed, pot-seal, and cyclone. From the results, they found a strong relationship between the solids flow pattern in the bubbling bed in the return system and superficial gas velocity in the riser.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a small number of studies based on a three dimensional model of a DCFB CLC unit may be found in the lit erature. Guan et al (2014Guan et al ( , 2016 conducted three dimensional (3D) numerical simulations of a cold flow model, scaled from a 30 MW model by Johansson et al (2003), and studied the effects of drag cor relation on the predictions and operating conditions on the solid cir culation rate. Geng et al (2015) used the 3D CFD for reproducing a 120 kW cold flow model of Pröll et al (2009b) and studied the effects of fluidization rate on the solid circulation.…”
Section: Introductionmentioning
confidence: 99%
“…A primeira, apesar de fisicamente mais próxima à realidade e, aparentemente, mais difundida em estudos que consideram somente o ciclone, como ressaltado por Dias (2009), gera um custo computacional maior (VAN WACHEM et al, 2001;CHIESA et al, 2005). Dessa forma, para sistemas com um número elevado de partículas e de volumes de controle na malha computacional, como os circuitos integrados de LFC, ainda se prefere a abordagem Euleriana, como demonstrado nos trabalhos apresentados por Wang et al (2014), Guan et al (2016), Yu et al (2018) e Liu, Zhang e Wang (2019).…”
Section: Introductionunclassified
“…Estes modelos foram utilizados nos trabalhos de Lu et al (2013), Wang et al (2014) e Liu, Zhang e Wang (2019). Todavia, os modelos que consideram o escoamento homogêneo, como o de Gidaspow, de 1994, ainda são amplamente aplicados, como verificado nos trabalhos apresentados por Seo et al (2011), Guan et al (2016), Wang et al (2017) e Wang et al (2018).…”
Section: Introductionunclassified